1996
DOI: 10.1099/00207713-46-1-155
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio ichthyoenteri sp. nov., a Pathogen of Japanese Flounder (Paralichthys olivaceus) Larvae

Abstract: Seven similar strains which were pathogens of Japanese flounder (Paralichthys olivaceus) larvae with opaque intestines had characteristics of the genus Vibrio. These strains were divided into two genomic species (species 1 containing six strains, and species 2 containing one strain) on the basis of the results of DNA-DNA hybridization experiments in which the membrane filter method was used, and these two species could be differentiated from each other by the following characteristics: acid production from D-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…Although V. ichthyoenteri was originally described as pathogenic for Japanese flounder larvae (Ishimaru et al 1996), our isolates were very infrequent in fish with clinical signs, and were clearly associated with asymptomatic individuals during the whole year. Whether these facts could be related to a protective or beneficial role against infection by other bacteria, as suggested for other Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although V. ichthyoenteri was originally described as pathogenic for Japanese flounder larvae (Ishimaru et al 1996), our isolates were very infrequent in fish with clinical signs, and were clearly associated with asymptomatic individuals during the whole year. Whether these facts could be related to a protective or beneficial role against infection by other bacteria, as suggested for other Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed the identification of the isolates at the genus and, in most cases, at the species level. The tentative identification of Vibrio ichthyoenteri, the only species not included in the previous references, was accomplished according to Ishimaru et al (1996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are closely associated with many kinds of marine organisms, from plankton to fish (Cerdà-Cuéllar et al, 1997;MacDonald et al, 1986;Nair et al, 1988;Onarheim et al, 1994;Simidu et al, 1969Simidu et al, , 1971Sochard et al, 1979). Some species are found as symbionts in specialized luminous organs of marine fish and invertebrates (Lee & Ruby, 1994;Leisman et al, 1980;Reichelt et al, 1977;Ruby & Asato, 1993;Ruby & Morin, 1978), whereas many other species are pathogens of humans or marine animals (Blake et al, 1980;Borrego et al, 1996;Egidius et al, 1986;Hada et al, 1984;Ishimaru et al, 1996;Schiewe et al, 1981). These halophilic, facultatively anaerobic, Gram-negative rods are known to include both nitrogen-fixers and denitrifiers (Guerinot & Colwell, 1985;Guerinot et al, 1982;Shieh & Lin, 1992Shieh & Liu, 1996;Shieh & Yang, 1997;Shieh et al, 1989), though the definitions given in Bergey's Manual of Systematic Bacteriology in 1984 indicated that these bacteria include neither nitrogen-fixers nor denitrifiers Baumann & Schubert, 1984;.…”
mentioning
confidence: 99%
“…Nodavirus causing viral nervous necrosis was described as the cause of high mortality in cultured Japanese flounder larvae (Nguyen et al 1994). An atypical strain of Aeromonas salmonicida has been associated with ulcerative skin disease in wild-caught and cultured adult flounder (Wiklund (Levin et al 1972), cultured turbot Scophthalmus maxjmus (Lupiani et al 1989, Grisez et al 1996 and cultured Japanese flounder larvae (Ishimaru et al 1996).…”
Section: Introductionmentioning
confidence: 99%